TEORI AGENCY DALAM PEMIKIRAN ORGANISASI ; PENDEKATAN POSITIVIST DAN PRINCIPLE-AGEN - Deddy Kurniawansyah; Sigit Kurnianto; Firdaus Aditya Rizqi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2018)
Agency theory has been used by researchers in accounting, economics, finance, marketing, political science, organizational behavior, and sociology. However, this theory is still surrounded by controversy. The purpose of this study is to describe the contribution of agency theory to organizations with a positivist and principalagent approach. This research method uses literature studies. The results of this study are agency theory giving two contributions specifically to organizational thinking. The first is the treatment of information. Organizations can intervene in information systems with the aim of controlling agent opportunism. The second is the risk implication. The organization is assumed to have uncertainty in the future. Results uncertainty combined with differences in willingness to accept risk will affect the contract between the principal and the agent. The idea of agency theory of risk, outcome uncertainty, incentives, and information systems is a new contribution to organizational thinking, and empirical evidence supports theory, especially when associated with complementary theoretical perspectives